Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Calculate the sum:

$$ \sum_{k=0}^n (-1)^k {n+1\choose k+1} $$

I don't know if I'm so tired or what, but I can't calculate this sum. The result is supposed to be $1$ but I always get something else...

share|improve this question
Hint: Use the binomial theorem to expand $(1-1)^{n+1}$. –  Henning Makholm Jul 29 '12 at 21:42
$ (x + 1)^n = \sum_{k = 0}^{n} {n \choose k} x^k. $ –  user2468 Jul 29 '12 at 21:47
Oh, @Henning: I typed my answer up, but it turns out I'm 5 minutes after your (earlier posted, yet containing more or less everything in my answer) comment. –  mixedmath Jul 29 '12 at 21:50
add comment

4 Answers 4

up vote 3 down vote accepted

Using the binomial theorem we have: $$ (1 + (-1))^{n+1} = {{n+1} \choose 0} (-1)^0 + {{n+1} \choose 1} (-1)^1 + \ldots + {{n+1} \choose {n+1}} (-1)^{n+1}.$$ "Divide" by ${-1}$ to get: $$ - (1 - 1)^{n+1} = -{{n+1} \choose 0} + \color{blue}{{{n+1} \choose 1} (-1)^0 + \ldots + {{n+1} \choose {n+1}} (-1)^{n}}.$$ This pretty much solves it.

share|improve this answer
add comment


  1. $\displaystyle (1-1)^{n+1} = \sum_{k = 0}^{n+1} {n \choose k}1^k(-1)^{n-k}$
  2. What terms are or aren't in your sum that are in the one above?
share|improve this answer
add comment

Another way to see it: prove that $$\binom{n}{k}+\binom{n}{k+1}=\binom{n+1}{k+1}\,\,\,,\,\,\text{so}$$ $$\sum_{k=0}^n(-1)^k\binom{n+1}{k+1}=\sum_{k=0}^n(-1)^k\cdot 1^{n-k}\binom{n}{k}+\sum_{k=0}^n(-1)^k\cdot 1^{n-k}\binom{n}{k+1}=$$ $$=(1+(-1))^n-\sum_{k=0}^n(-1)^{k+1}\cdot 1^{n-k-1}\binom{n}{k+1}=0-(1-1)^n+1=1$$

share|improve this answer
add comment

$$\sum_{k=0}^n (-1)^k {n+1\choose k+1}=-\sum_{k=0}^n (-1)^{k+1} {n+1\choose k+1}= $$ $$=-\left(\sum_{k=0}^n (-1)^{k+1} {n+1\choose k+1}\right)=$$ $$=-\left(\sum_{j=1}^{n+1} (-1)^{j} {n+1\choose j}+(-1)^{0} {n+1\choose 0}-(-1)^{0} {n+1\choose 0}\right)= $$ $$=-\left(\sum_{j=0}^{n+1} (-1)^{j} {n+1\choose j}-(-1)^{0} {n+1\choose 0}\right)=-(1-1)^{n+1}+1=1$$

share|improve this answer
add comment

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.